THE INFLUENCE OF INTERNAL ENVIRONMENTAL UNCERTAINTY ON LOYALTY IN BANKING - zaenal aripin; Kosasih; Vip Paramarta (Organisasi Kreatif Indonesia Emas, 2023)
Beckground: The uncertainty of the internal environment is one of the main challenges faced by banks in achieving customer loyalty. The internal environment of banks often changes dynamically, including changes in internal policies, organizational structure, and service quality. The uncertainty of the internal environment can affect customers' perception of service quality and may impact their level of loyalty to the bank. Therefore, it is important to understand the effect of internal environmental uncertainty on customer loyalty in the banking sector. Aims: The purpose of this study is to identify and analyze the effect of internal environmental uncertainty on loyalty in the banking sector. This study aims to provide better insight into how changes in the internal environment within banks can affect customer loyalty. Research Method: This research utilizes a quantitative approach using survey as the data collection method. The research sample consisted of 60 randomly selected bank customers. Respondents were asked to rate the level of internal environmental uncertainty they experience in relation to the bank they use, as well as their level of loyalty to the bank. The data collected was then analyzed using appropriate statistical techniques to test the research hypotheses. Results and Conclusions: The results of this study indicate a significant influence between internal environmental uncertainty and customer loyalty in the banking sector. The higher the level of internal environmental uncertainty experienced by customers, the lower their level of loyalty to the bank. This suggests that changes in the bank's internal environment can affect customers' perceptions and possibly influence their decision to remain loyal to the bank. Contribution: This research makes an important contribution to the understanding of the factors that influence customer loyalty in the banking sector. By understanding the influence of internal environmental uncertainties, banks can take appropriate actions to manage changes and improve customer loyalty levels. The results of this study can also be used as a basis for developing more effective marketing strategies in the face of internal environmental uncertainty.